Single metal catalysis: DFT and CAS modelling of species involved in the Fe cation assisted transformation of acetylene to benzene. (17th September 2017) - Altun, Zikri; Bleda, Erdi; Trindle, Carl
ABSTRACT: Gas phase conversion of acetylene to benzene, assisted by a single metal cation such as Fe(+), Ru(+) and Rh(+), offers an attractive prospect for application of computational modelling techniques to catalytic processes. Gas phase processes are not complicated by environmental effects and the participation of a single metal atom is a significant simplification. Still the process is complex, owing to the possibility of several low-energy spin states and the abundance of alternative structures. By density functional theory modelling using recently developed models with range and dispersion corrections, we locate and characterise a number of extreme points on the FeC6 H6 (+) surface, some of which have not been described previously. These include eta-1, eta-2 and eta-3 complexes of Fe(+) with the C4 H4 ring. We identify new FeC6 H6 (+) structures as well, which may be landmarks for the Fe(+)-catalysed production of benzene from acetylene. The Fe(+) benzene complex is the most stable species on the FeC6 H6 cation surface. With the abundant energy of complexation available in the isolated gas phase species, detachment of the Fe(+) and production of benzene can be efficient. We address the issue raised by other investigators whether multi-configurational self-consistent field methods are essential to the proper description of these systems. We find that the relative energy of intrinsically multi-determinant doublets is strongly affected, but judge that the density functional theory (DFT) description provides more accurate estimates of energetics and a more plausible reaction path. Abstract :